Long-Term Inhibition of Xanthine Oxidase by Febuxostat Does Not Decrease Blood Pressure in Deoxycorticosterone Acetate (DOCA)-Salt Hypertensive Rats - Szasz, Theodora (Public Library of Science, 2013)
Xanthine oxidase and its products, uric acid and ROS, have been implicated in the pathogenesis of cardiovascular disease, such as hypertension. We have previously reported that allopurinol inhibition of XO does not alter the progression of deoxycorticosterone acetate (DOCA)-salt hypertension in rats. However other researchers have observed a reduction in blood pressure after allopurinol treatment in the same model. To resolve this controversy, in this study we used the newer and more effective XO inhibitor febuxostat, and hypothesized that a more complete XO blockade might impair hypertension development and its end-organ consequences. We used DOCA-salt hypertensive rats and administered vehicle (salt water) or febuxostat (orally, 5 mg/kg/day in salt water) in a short-term “reversal” experiment (2 weeks of treatment 3 weeks after DOCA-salt beginning) and a long-term “prevention” experiment (treatment throughout 4 weeks of DOCA-salt). We confirmed XO inhibition by febuxostat by measuring circulating and tissue levels of XO metabolites. We found an overall increase in hypoxanthine (XO substrate) and decrease in uric acid (XO product) levels following febuxostat treatment. However, despite a trend for reduced blood pressure in the last week of long-term febuxostat treatment, no statistically significant difference in hemodynamic parameters was observed in either study. Additionally, no change was observed in relative heart and kidney weight. Aortic media/lumen ratio was minimally improved by long-term febuxostat treatment. Additionally, febuxostat incubation in vitro did not modify contraction of aorta or vena cava to norepinephrine, angiotensin II or endothelin-1. We conclude that XO inhibition is insufficient to attenuate hypertension in the rat DOCA-salt model, although beneficial vascular effects are possible.